HPV involvement in tonsillar cancer: prognostic significance and clinically relevant markers - Rotnáglová, Eliška; Tachezy, Ruth; Saláková, Martina; Procházka, Bohumír; Košl'abová, Eva; Veselá, Eva; Ludvíková, Viera; Hamšíková, Eva; Klozar, Jan (International journal of cancer, 2011)
The association of high-risk human papillomaviruses (HR HPVs) with tonsillar cancer (TC) has been documented. Because patients with HPV-associated tumors show better survival rates, modification of their treatment regimen is being considered. It is therefore crucial to find markers for the identification of patients whose tumors are linked to viral infection. A cohort of 109 patients with primary TC was screened for HPV DNA presence in the tumor tissues and HPV-specific antibodies in sera. Data regarding risk factors and clinical parameters were collected. Forty-five specimens were analyzed for the expression of viral E6 and E2-region mRNA, and the p16 and p53 protein expression status was assessed by immunohistochemistry. The overall prevalence of HPV DNA in TC tissues was 65.1%. Ninety-three percent of HR HPV DNA-positive samples expressed E6*I mRNA. E2-region mRNA expression was detected in 36% of positive samples, which implies that the virus is integrated in 64% of HPV DNA/RNA-positive tumors. p16 overexpression and the presence of antibodies specific to HPV16 E6/E7 oncoproteins correlated well with HPV DNA and RNA presence. The disease-specific survival rate of patients with HPV DNA-positive tumors was significantly higher than that of HPV DNA-negative patients. In addition to providing further evidence of the involvement of HPV infection in the etiopathogenesis of a proportion of TC cases, our study demonstrates that p16 immunostaining and anti-E6/E7 antibodies as surrogate markers of HPV involvement represent specific, sensitive and clinically accessible assays for the identification of TC patients who have a considerably better prognosis.
Keywords: Tonsillar Neoplasms; polymerázová řetězová reakce; Male; kohortové studie; protilátky virové; tonzilární nádory; Cohort Studies; prognóza; Tumor Virus Infections; Adult; DNA, Viral; dospělí; imunohistochemie; mužské pohlaví; DNA virů; lidé; ženské pohlaví; Immunohistochemistry; Papillomaviridae; Biomarkers, Tumor; infekce onkogenními viry; Humans; Prognosis; Antibodies, Viral; Polymerase Chain Reaction; Female; lidé středního věku; nádorové biomarkery; Middle Aged